Continuous photofermentative production of hydrogen by immobilized Rhodobacter sphaeroides O.U.001. (27th April 2015) - Zagrodnik, R.; Seifert, K.; Stodolny, M.; Laniecki, M.
Abstract: Photofermentative hydrogen production applying Rhodobacter sphaeroides O.U.001 immobilized on porous glass plates or porous and non-porous glass beads in presence of malic acid (Biebl and Pfennig medium) was studied under continuous and semicontinuous conditions. The applied bacteria operating under continuous regime showed the best performance and stability while immobilized on porous glass plate modified with (3-(2-aminoethyl)aminopropyl)trimetoxysilane (AEAPTMS). Here, the total amount of produced hydrogen was 4.19 L/reactor whereas average hydrogen production rate was 12.7 mL/L medium/h at hydraulic retention time (HRT) of 22 h. For experiments in suspension cumulative hydrogen amount was only 2.39 L/reactor. Accumulation of VFA's (mainly formic acid) in reaction medium as well as accumulation of biomass on supports was responsible for the decreasing activity. Comparison of different parameters in experiments with porous and non-porous glass beads proved that HRT plays a crucial role in photofermentative hydrogen production. Graphical abstract: Highlights: Application of porous and non-porous glass for immobilization of R. sphaeroides . Utilization of flat plate photobioreactor for continuous hydrogen production. Glass silanized with AEAPTMS showed superior H2 production activity. Amount of immobilization carrier have great effect on H2 production capacity. Control of hydraulic retention time play a crucial role in hydrogen production rate.